(untitled) (Global Journal of Management and Business Research, 2023)
Last mile delivery LMD focuses on the final step in the supply chain and continues the most expensive aspect of providing home delivery In Saudi Arabia the development of the LMD Further the challenges and successes of similar companies in Saudi Arabia were examined so as to provide insight into market opportunity This is all taking place within the context of the ongoing Covid-19 pandemic and thus this research has examined how companies reacted strategically during and post Covid Logistics considered to be an integral part of Saudi Arabia 2030 vision as the Kingdom has positioned itself to become the new logistics hub for the Middle East In order to contribute to this area in both an academic and practical way this research provided an analysis